Pengaruh Struktur Aset, Pertumbuhan Penjualan dan Struktur Modal terhadap Kebijakan Utang - Sari, Silvia; Uci, Uci (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
One important element in a company is the existence of adequate capital to support the company's business activities. Therefore, debt policy can be a funding option to boost company finances which is useful for supporting operational needs. However, to prevent losses, companies must be able to manage funding sources effectively, so the aim of this research is to empirically determine the influence of asset structure, sales growth and capital structure on debt policy, both partially and simultaneously. This research was conducted by analyzing the financial reports of companies in the food and beverage sector listed on the Indonesia Stock Exchange (BEI) during the period 2019 to 2023. The sample used in this research was 17 food and beverage sector companies listed on the Stock Exchange Indonesia during the period 2019 to 2023 using a purposive sampling technique. The data used in this research is secondary data in the form of financial reports from each company that has been used as a research sample. The panel data regression method was used as the research methodology in this study. Analysis of research results using Eviews 12 software. The research results show that the best model is the Random Effect Model (REM). The results of this research show that asset structure, sales growth and capital structure simultaneously influence debt policy, and partially capital structure influences debt policy, asset structure has no influence on debt policy and sales growth has no influence on debt policy.